2000
DOI: 10.1063/1.126490
|View full text |Cite
|
Sign up to set email alerts
|

Deep levels in high-energy proton-irradiated tin-doped n-type Czochralski silicon

Abstract: A deep level transient spectroscopy study of defects created by 61 MeV proton irradiation of tin-doped n-type Czochralski silicon is reported. A comparison is made with the deep levels observed in irradiated p–n junction diodes fabricated in n-type float-zone silicon, without tin doping. The main conclusions are that in Sn-doped material, at least two additional deep radiation centers are introduced at 0.29±0.01 and 0.61±0.02 eV below the conduction band. From annealing experiments, it is concluded that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
2
20
1
5
Order By: Relevance
“…[129][130][131][132] In recent studies, it was shown that Sn doping can impact the diffusion and formation of A-centers in Si. 23,113 Critical in this aspect is the formation of SnVO clusters, which are very bound and less mobile than the VO.…”
Section: Sn Doping In Simentioning
confidence: 99%
See 1 more Smart Citation
“…[129][130][131][132] In recent studies, it was shown that Sn doping can impact the diffusion and formation of A-centers in Si. 23,113 Critical in this aspect is the formation of SnVO clusters, which are very bound and less mobile than the VO.…”
Section: Sn Doping In Simentioning
confidence: 99%
“…144 It deserves noting that Pb in Si does not introduce, to the best of our knowledge, any levels from radiationinduced defects in the forbidden gap in comparison with Sn. 129,133 These levels in Sn-doped Si may act as recombination centers deteriorating the performance of solar cells. In this respect, the absence of such levels in Pd-doped Si is an advantage in comparison to Sn-doped Si.…”
Section: Pb Doping In Simentioning
confidence: 99%
“…Since Sn does not create energy levels in Si band gap (E g ), tin doping does not affect electrical, optical and recombination properties of Si crystals. At the same time, Sn atoms available in Si significantly slow down the degradation of these characteristics caused by heating [4][5][6] and radiation [6][7][8]. The first reports about crystallization of Si a  films doped by Sn from the gaseous phase in the process of film formation were made in [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sn is an isovalent dopant that is considerably larger than Si, so it can strongly bind with vacancies and thus it can influence the vacancy-related defects and the generation rate of interstitial-related defects [42][43][44][45]. It was previously determined that Sn doping and in particular high concentration Sn doping will significantly impact the formation and diffusion of A-centers in Si (refer to Figure 5) [39][40][41]46].…”
Section: Isovalent Doping In Siliconmentioning
confidence: 99%